Descriptive Study of Pediatric Patients with Ileum Stoma at Inpatient Installation of Dr. Soetomo General Hospital Surabaya - Farihazqa Hafez Mikala; Alpha Fardah Athiyyah; I Gusti Bagus Adria Hariastawa; I Gusti Made Reza Gunadi Ranuh (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Ileostomy is needed as an important part of the management of several congenital disorders of the intestine. One of the indication of ileostomy in children is short bowel syndrome, which is caused by intestinal atresia such as ileal atresia and intussusception. Ileostomy is a surgery procedure which consists of creating holes on abdominal walls to release stool. The objective of this study was to determine the description of pediatric patients who underwent ileostomy in Dr. Soetomo General Hospital Surabaya. Methods: This was a retrospective descriptive study on medical records in the Central Medical Record Department of Pediatrics and General Surgery Dr. Soetomo General Hospital Surabaya from January 2017 to December 2018. Results: There were 26 pediatric patients who underwent ileostomy in Dr. Soetomo General Hospital Surabaya. Samples from male patients consisted of 57.7%, while female patients consisted of 42.3% with the most common age group was neonates with 57.7%, infants 30.8%, and toddlers 11.5%. There were 30.7% patients with 2.0-2.9 kg body weight, 27% with 3.0-3.9 kg body weight, and 42.3% with more than 4 kg body weight. The outcome showed that repair was needed, or the patient was discharged with periodic follow-up after ileostomy. Conclusion: Ileostomy was performed mostly in neonates with average weight within normal body mass index (BMI) and the highest incidence of pediatric patient with ileum stoma was in pediatric patients.